2010
DOI: 10.1111/j.1399-6576.2010.02333.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous adductor-canal-blockade for adjuvant post-operative analgesia after major knee surgery: preliminary results

Abstract: Because both the saphenous nerve and in part the obturator nerve are traversing the adductor canal of the thigh, we hypothesised that repeated administration of a local anaesthetic (LA) into this aponeurotic space could be a useful option for post-operative analgesia after knee replacement surgery. A systematic search of the literature pertinent to the blockade of the saphenous and/or obturator nerves for pain relief after knee surgery was conducted. Further, pain and opioid requirements were evaluated in eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
164
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(176 citation statements)
references
References 19 publications
4
164
0
8
Order By: Relevance
“…The primary benefit of an adductor canal block is to provide analgesia while limiting loss of quadriceps strength, presumably by blocking only the saphenous nerve, the nerve to the vastus medialis, and potentially the articular contribution of the obturator nerve to the knee joint. [10][11][12] We did not objectively measure quadriceps strength due to the outpatient nature of the primary surgical procedure. Indirectly, all patients were able to stand in the PACU, and no study participant mentioned subjective leg weakness or reported falls at the 24-hr follow-up interview.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary benefit of an adductor canal block is to provide analgesia while limiting loss of quadriceps strength, presumably by blocking only the saphenous nerve, the nerve to the vastus medialis, and potentially the articular contribution of the obturator nerve to the knee joint. [10][11][12] We did not objectively measure quadriceps strength due to the outpatient nature of the primary surgical procedure. Indirectly, all patients were able to stand in the PACU, and no study participant mentioned subjective leg weakness or reported falls at the 24-hr follow-up interview.…”
Section: Discussionmentioning
confidence: 99%
“…9 The adductor canal block may provide superior analgesia over traditional distal saphenous nerve blocks for surgical procedures of the knee because this block includes the saphenous nerve, the nerve to the vastus medialis, and potentially the articular contribution of the obturator nerve to the knee joint. [10][11][12][13] Our primary hypothesis was that performing an adductor canal block as part of a multimodal analgesic regimen would result in improved analgesia immediately following arthroscopic medial meniscectomy.…”
Section: Résumémentioning
confidence: 99%
“…The adductor canal is found in the middle 1/3 of the thigh and runs from the apex of the femoral triangle proximally to the adductor hiatus distally. Because the adductor canal consistently encloses the saphenous nerve and the nerve to the vastus medialis, placement of a catheter within the canal can potentially spare the major motor branches of the femoral nerve while still providing effective pain relief [19,22]. While the adductor canal technique may preserve quadriceps muscle strength compared to the femoral nerve block in volunteers, the effects, if any, on postoperative rehabilitation and discharge eligibility for actual patients undergoing TKA still remain to be studied [19].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our trial, Kaloul et al [8] suggest that obturator nerve involvement does not improve postoperative pain scores after TKR; Morin et al [9] come to the same conclusion. Preliminary results by Lund et al go in the opposite direction: continuous adductor-canal-blockade may be a valuable adjunct for post-operative analgesia after major knee surgery [12]. With this scenario we can affirm that, both for the intraoperative and postoperative period after TKR, the role of obturator nerve block remains unclear and further trials are therefore necessary to clarify this aspect.…”
Section: Discussionmentioning
confidence: 93%